Preparation method and application of wood-based heavy metal adsorbent
By carboxylation modification of wood-based materials, the problem of insufficient selectivity and low adsorption capacity of wood-based materials in heavy metal ions is solved, and efficient adsorption and rapid separation of a variety of heavy metal ions is achieved.
Patent Information
- Application Number
- CN202411107333.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The existing wood-based materials have problems of insufficient selectivity and low adsorption capacity in the adsorption of heavy metal ions, which limits their effectiveness in practical applications.
By carboxylation modification of the wood-based material, it includes the addition of N,N-dimethylformamide, catalyst and epoxypropane to the reactor for reaction, followed by dropping sodium hydroxide solution, and reaction under different temperatures and pH conditions, finally obtaining a wood-based heavy metal adsorbent.
The selectivity and adsorption amount of heavy metal ions of wood-based materials are significantly improved, and efficient adsorption and rapid separation of Fe(II), Fe(III), Cr(III) and Cr(VI).
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heavy metal ion treatment, and more particularly to a preparation method and application of a wood-based heavy metal adsorbent. Background Art
[0002] Water is vital to the ecosystem and human society, and its purity directly affects health and survival. However, heavy metal ions in water bodies pose a serious threat to human health and environmental safety due to their strong toxicity and high bioaccumulation. Therefore, effective treatment and removal of heavy metal ions in water can not only protect water resources from pollution and ensure the safety of various water bodies, but also help maintain ecological balance and promote sustainable development. Developing efficient and environmentally friendly water treatment technologies to remove or reduce the concentration of heavy metal ions is an important task facing the current field of environmental science and engineering.
[0003] As a natural polymer material, wood-based materials are porous, renewable and low-cost. In addition, their excellent mechanical strength and plasticity enable them to maintain good stability under various environmental conditions.
[0004] However, the use of wood-based materials for the adsorption of heavy metal ions has the problems of insufficient selectivity and low adsorption capacity, which limits its effectiveness in practical applications. If the surface of wood-based materials is carboxylated, it can not only enhance its selective adsorption capacity for heavy metal ions, but also significantly increase the adsorption amount due to the strong coordination effect between carboxyl groups and heavy metal ions. This modification strategy has opened up a new method for the application of wood-based materials in the field of heavy metal ion treatment. Summary of the invention
[0005] In view of this, the present invention provides a preparation method and application of a wood-based heavy metal adsorbent to solve the threat to the natural ecology caused by excessive heavy metal content in many water bodies.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a wood-based heavy metal adsorbent comprises the following steps:
[0008] (1) placing a wood block in a reaction kettle, adding N,N-dimethylformamide and a catalyst, dropping epichlorohydrin during the stirring process, and reacting for a period of time after the dropping is completed; cooling, then dropping sodium hydroxide solution, and continuing to react for a period of time after heating, and then washing with distilled water for 3-5 times to obtain an epoxy-terminated wood-based material;
[0009] (2) placing the epoxy-terminated wood-based material into a reaction kettle, adding ethylenediamine and N,N-dimethylformamide, heating the reaction for a period of time under nitrogen protection, naturally cooling to room temperature, washing with distilled water for 3-5 times, and then vacuum drying or naturally drying to obtain an amino-modified wood-based material;
[0010] (3) The aminated wood-based material is placed in a reactor, sodium chloroacetate and water are added, the pH is adjusted while the temperature is increased, and the reaction is terminated when the pH remains unchanged for a period of time. The material is naturally cooled to room temperature, washed with distilled water for 3-5 times, and then vacuum dried or naturally air-dried to obtain a wood-based heavy metal adsorbent.
[0011] Preferably, the amount of N,N-dimethylformamide added in step (1) is 200-300 mL;
[0012] The mass ratio of the wood block, epichlorohydrin and sodium hydroxide solution is: (30-50): (61.7-102.8): (33.4-55.6).
[0013] Preferably, the catalyst in step (1) is boron trifluoride diethyl ether;
[0014] The dripping speed of the epichlorohydrin is 20-60 drops / min;
[0015] The concentration of the sodium hydroxide solution is 20-30%.
[0016] Preferably, after the dropwise addition in step (1) is completed, the reaction period is reflux at a constant temperature of 40-80° C. for 1-6 hours;
[0017] The cooling is to cool to below 40°C;
[0018] The step of continuing the reaction for a period of time after the temperature is raised is to raise the temperature to 65-85° C. and continue the reaction at a constant temperature for 2-6 hours.
[0019] Preferably, the mass ratio of the terminal epoxy wood-based material to ethylenediamine in step (2) is (30-50): (20-33.4);
[0020] The amount of N,N-dimethylformamide added is 300-8000mL.
[0021] Preferably, the heating reaction period in step (2) is heating to 50-90° C. for 2-8 hours.
[0022] Preferably, the mass ratio of the aminated wood-based material to sodium chloroacetate in step (3) is: (30-50): (16.1-26.8);
[0023] The amount of water added is 500-1000mL.
[0024] Preferably, the heating in step (3) is to 75-100° C.;
[0025] The pH is adjusted to pH>10;
[0026] The pH is kept constant for a period of time of 0.5 h.
[0027] Preferably, the solution used to adjust the pH is a sodium hydroxide solution with a concentration of 20-40%.
[0028] Another object of the present invention is to provide an application of the wood-based heavy metal adsorbent obtained by the preparation method of the above-mentioned wood-based heavy metal adsorbent in heavy metal adsorption, specifically: using the wood-based heavy metal adsorbent to adsorb Fe(II), Fe(III), Cr(III), and Cr(VI) under the conditions of pH 1-6 and temperature >10°C.
[0029] It can be seen from the above technical solution that compared with the prior art, the present invention has the following technical effects:
[0030] The adsorbent prepared by the present invention uses wood as a substrate, has a low production cost, and has high material porosity and strong mechanical properties, and can achieve efficient adsorption and rapid separation of heavy metals. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] This embodiment provides a method for preparing a wood-based heavy metal adsorbent, comprising the following steps:
[0034] (1) 30 parts of wood blocks of a certain size are placed in a reactor, 200 mL of N,N-dimethylformamide (DMF) is added, and 1 part of boron trifluoride diethyl ether is added as a catalyst. During the stirring process, 61.7 parts of epichlorohydrin are added dropwise at a rate of about 60 drops / min. After the addition is completed, the mixture is refluxed at a constant temperature of 40° C. for 6 hours; then the mixture is naturally cooled to below 40° C., 33.4 parts of a 30% aqueous solution of sodium hydroxide is slowly added dropwise to the mixture, and the mixture is heated to 75° C. and the reaction is continued at a constant temperature for 3 hours; after washing with distilled water for 4 times, an epoxy-terminated wood-based material is obtained.
[0035] (2) 30 parts of the epoxy-terminated wood-based material were placed in a reaction kettle, and 20.0 parts of ethylenediamine and 300 mL of DMF were added. The temperature was raised to 50° C. under nitrogen protection for reaction for 8 h, and the mixture was naturally cooled to room temperature. The mixture was washed with distilled water for 4 times and then vacuum dried or naturally air-dried to obtain the amino-terminated wood-based material.
[0036] (3) 30 parts of the amino wood-based material were placed in a reactor, 16.1 parts of sodium chloroacetate and 500 mL of water were added, the temperature was raised to 75°C for reaction, and the pH of the reaction solution was adjusted to above 10 with 40% sodium hydroxide solution. The reaction was terminated when the pH remained unchanged for 0.5 h, and the reaction mixture was naturally cooled to room temperature. The mixture was washed with distilled water 5 times and then vacuum dried or naturally air-dried to obtain a new wood-based heavy metal adsorbent.
[0037] This new wood-based heavy metal adsorbent is used for the adsorption and removal of Fe(III). Under the conditions of pH 3 and temperature 25°C, its adsorption capacity can reach 280 mg / g.
[0038] Example 2
[0039] (1) 50 parts of wood blocks of a certain size are placed in a reactor, 300 mL of N,N-dimethylformamide (DMF) is added, and 0.9 parts of boron trifluoride diethyl ether is added as a catalyst. During the stirring process, 102.8 parts of epichlorohydrin are added dropwise at a rate of about 50 drops / min. After the addition is completed, the mixture is refluxed at a constant temperature of 70° C. for 2 hours; then the mixture is naturally cooled to below 40° C., 55.6 parts of a 25% aqueous solution of sodium hydroxide is slowly added dropwise to the mixture, and the mixture is heated to 85° C. and the reaction is continued at a constant temperature for 2 hours; after washing with distilled water for 3 times, an epoxy-terminated wood-based material is obtained.
[0040] (2) 30 parts of the epoxy-terminated wood-based material were placed in a reaction kettle, and 20.0 parts of ethylenediamine and 500 mL of DMF were added. The temperature was raised to 90° C. under nitrogen protection for reaction for 2 h, and the mixture was naturally cooled to room temperature. The mixture was washed with distilled water for 4 times and then vacuum dried or naturally air-dried to obtain the amino-terminated wood-based material.
[0041] (3) 50 parts of the amino wood-based material were placed in a reactor, 26.8 parts of sodium chloroacetate and 800 mL of water were added, the temperature was raised to 100°C for reaction, and the pH of the reaction solution was adjusted to above 10 with 20% sodium hydroxide solution. The reaction was terminated when the pH remained unchanged for 0.5 h, and the reaction mixture was cooled naturally to room temperature. The mixture was washed with distilled water 4 times and then vacuum dried or naturally air-dried to obtain a new wood-based heavy metal adsorbent.
[0042] This new wood-based heavy metal adsorbent is used for the adsorption and removal of Cr(III). Under the conditions of pH 3.5 and temperature 35°C, its adsorption capacity can reach 430 mg / g.
[0043] Example 3
[0044] This embodiment provides a method for preparing a wood-based heavy metal adsorbent, comprising the following steps:
[0045] (1) 50 parts of wood blocks of a certain size are placed in a reactor, 300 mL of N,N-dimethylformamide (DMF) is added, and 2.5 parts of boron trifluoride diethyl ether are added as a catalyst. During the stirring process, 102.8 parts of epichlorohydrin are added dropwise at a rate of about 30 drops / min. After the addition is completed, the mixture is refluxed at a constant temperature of 80° C. for 1 hour; then the mixture is naturally cooled to below 40° C., 55.6 parts of a 20% aqueous solution of sodium hydroxide are slowly added dropwise to the mixture, and the mixture is heated to 65° C. and the reaction is continued at a constant temperature for 6 hours; after washing with distilled water for 3 times, an epoxy-terminated wood-based material is obtained.
[0046] (2) 50 parts of the epoxy-terminated wood-based material were placed in a reaction kettle, and 33.4 parts of ethylenediamine and 800 mL of DMF were added. The temperature was raised to 80° C. under nitrogen protection for 4 hours, and the mixture was naturally cooled to room temperature. The mixture was washed with distilled water for 4 times and then vacuum dried or naturally air-dried to obtain the amino-terminated wood-based material.
[0047] (3) 50 parts of the amino wood-based material were placed in a reactor, 26.8 parts of sodium chloroacetate and 1000 mL of water were added, the temperature was raised to 90°C for reaction, and the pH of the reaction solution was adjusted to above 10 with 30% sodium hydroxide solution. The reaction was terminated when the pH remained unchanged for 0.5 h, and the reaction mixture was naturally cooled to room temperature. The mixture was washed with distilled water 4 times and then vacuum dried or naturally air-dried to obtain a new wood-based heavy metal adsorbent.
[0048] This new wood-based heavy metal adsorbent is used for the adsorption and removal of Cr(III). Under the conditions of pH 4 and temperature 25°C, its adsorption capacity can reach 480 mg / g.
[0049] Example 4
[0050] This embodiment provides a method for preparing a wood-based heavy metal adsorbent, comprising the following steps:
[0051] (1) 40 parts of wood blocks of a certain size are placed in a reactor, 250 mL of N,N-dimethylformamide (DMF) is added, and 1.5 parts of boron trifluoride diethyl ether are added as a catalyst. During the stirring process, 82.3 parts of epichlorohydrin are added dropwise at a rate of about 20 drops / min. After the addition is completed, the mixture is refluxed at a constant temperature of 65° C. for 3 hours; then the mixture is naturally cooled to below 40° C., 44.5 parts of a 25% aqueous solution of sodium hydroxide is slowly added dropwise to the mixture, and the mixture is heated to 80° C. and the reaction is continued at a constant temperature for 3 hours; after washing with distilled water for 4 times, the end-epoxy wood-based material is obtained.
[0052] (2) 40 parts of the end-epoxy wood-based material were placed in a reaction kettle, and 26.7 parts of ethylenediamine and 600 mL of DMF were added. The temperature was raised to 60° C. under nitrogen protection for reaction for 7 h, and the mixture was naturally cooled to room temperature. The mixture was washed with distilled water for 4 times and then vacuum dried or naturally air-dried to obtain the amino-modified wood-based material.
[0053] (3) 40 parts of the amino wood-based material were placed in a reactor, 21.4 parts of sodium chloroacetate and 800 mL of water were added, the temperature was raised to 80°C for reaction, and the pH of the reaction solution was adjusted to above 10 with 35% sodium hydroxide solution. The reaction was terminated when the pH remained unchanged for 0.5 h, and the reaction mixture was cooled naturally to room temperature. The mixture was washed with distilled water 5 times and then vacuum dried or naturally air-dried to obtain a new wood-based heavy metal adsorbent.
[0054] This new wood-based heavy metal adsorbent is used for the adsorption and removal of Cr(VI). Under the conditions of pH 2 and temperature 35°C, its adsorption capacity can reach 565 mg / g.
[0055] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0056] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. Application of a wood-based heavy metal adsorbent in heavy metal adsorption, characterized in that: Wood-based heavy metal adsorbents were used to adsorb Fe(II), Fe(III), Cr(III), and Cr(VI) at pH 1-6 and temperature >10°C; The preparation method of the wood-based heavy metal adsorbent comprises the following steps: (1) Put the wood block into a reactor, add N,N-dimethylformamide and a catalyst, add epichlorohydrin dropwise during the stirring process, and react for a period of time after the addition is completed; cool down, then add sodium hydroxide solution dropwise, and continue to react for a period of time after heating, and then wash to obtain the end-epoxy wood-based material; (2) placing the epoxy-terminated wood-based material into a reaction kettle, adding ethylenediamine and N,N-dimethylformamide, heating the reaction for a period of time under nitrogen protection, naturally cooling to room temperature, washing, and drying to obtain an amino-modified wood-based material; (3) The aminated wood-based material is placed in a reactor, sodium chloroacetate and water are added, the pH is adjusted while the temperature is increased, and the reaction is terminated when the pH remains constant for a period of time. The mixture is naturally cooled to room temperature, washed, and dried to obtain a wood-based heavy metal adsorbent.
2. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 1, characterized in that: The amount of N,N-dimethylformamide added in step (1) is 200-300 mL; The mass ratio of the wood block, epichlorohydrin and sodium hydroxide solution is: (30-50): (61.7-102.8): (33.4-55.6).
3. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 1, characterized in that: The catalyst in step (1) is boron trifluoride diethyl ether; The dripping speed of the epichlorohydrin is 20-60 drops / min; The mass concentration of the sodium hydroxide solution is 20-30%.
4. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 1, characterized in that: After the dropwise addition in step (1) is completed, the reaction period is 1-6 hours at a constant temperature of 40-80°C under reflux; The cooling is to cool to below 40°C; The step of continuing the reaction for a period of time after the temperature is raised is to raise the temperature to 65-85° C. and continue the reaction at a constant temperature for 2-6 hours.
5. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 1, characterized in that: The mass ratio of the terminal epoxy wood-based material to ethylenediamine in step (2) is (30-50): (20-33.4); The amount of N,N-dimethylformamide added is 300-8000 mL.
6. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 1, characterized in that: The temperature-raising reaction period in step (2) is 50-90° C. for 2-8 hours.
7. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 1, characterized in that: The mass ratio of the aminated wood-based material to sodium chloroacetate in step (3) is: (30-50): (16.1-26.8); The amount of water added is 500-1000mL.
8. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 1, characterized in that: The heating in step (3) is to heat to 75-100°C; The pH is adjusted to pH>10; The pH is kept constant for a period of time of 0.5 h.
9. The use of the wood-based heavy metal adsorbent in heavy metal adsorption according to claim 8, characterized in that: The solution used for adjusting the pH is a sodium hydroxide solution with a mass concentration of 20-40%.
Citation Information
Patent Citations
Cellulose-base chelated fiber and its synthesizing method and use
CN101070673A
High-strength honeycomb activated carbon and preparation method thereof
CN117839644A